2015
DOI: 10.1136/bmjopen-2015-008952
|View full text |Cite
|
Sign up to set email alerts
|

The Horsens-Aarhus Femoro Acetabular Impingement (HAFAI) cohort: outcome of arthroscopic treatment for femoroacetabular impingement. Protocol for a prospective cohort study

Abstract: IntroductionDuring the past decade, it has become increasingly more common to offer hip arthroscopic surgery when treating people with femoroacetabular impingement (FAI). Nevertheless, the latest reviews conclude that it still remains to be properly investigated how surgery affects the patients. Specifically, detailed information on the functional, muscular and mechanical impact of surgery in larger groups is lacking. Furthermore, the long-term outcome of the surgery is still to be investigated.Methods and ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Patients were recruited consecutively from December 2014 to February 2017 from the HAFAI-cohort (patients in Horsens and Aarhus with Femoral Acetabular Impingement) consisting of patients scheduled for hip arthroscopic treatment for FAIS at Horsens Regional Hospital, Denmark [19]. This cohort is followed prospectively to evaluate the outcome of arthroscopic treatment for FAIS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients were recruited consecutively from December 2014 to February 2017 from the HAFAI-cohort (patients in Horsens and Aarhus with Femoral Acetabular Impingement) consisting of patients scheduled for hip arthroscopic treatment for FAIS at Horsens Regional Hospital, Denmark [19]. This cohort is followed prospectively to evaluate the outcome of arthroscopic treatment for FAIS.…”
Section: Methodsmentioning
confidence: 99%
“…Following surgery, the patients followed a standardized, homebased rehabilitation programme instructed by experienced physiotherapists [19].…”
Section: Methodsmentioning
confidence: 99%
“…My PhD included studies on patients with femoroacetabular impingement syndrome (FAIS). We performed (1) a systematic review with meta-analysis1 investigating patient-reported outcomes before and after hip arthroscopic surgery in patients with FAIS; and (2) a cohort study in which I investigated patient-reported outcomes, hip muscle strength and physical activity level in 60 patients with FAIS before and after hip arthroscopic surgery 2–5…”
Section: What Did I Do?mentioning
confidence: 99%
“…The cohort study was conducted at Horsens Regional Hospital and Aarhus University in Denmark, where I tested all patients in an isokinetic dynamometer (figure 1)3 4 and attached accelerometers to their thigh in order to monitor daily activity level for 5 days 5. Patient-reported outcomes were collected using the Copenhagen Hip and Groin Outcome Score (HAGOS) 2. Furthermore, age-matched and gender-matched persons reporting no hip problems were included for comparison.…”
Section: How Did I Do It?mentioning
confidence: 99%
See 1 more Smart Citation